Oleuropein Transcriptionally Primes Lactobacillus plantarum to Interact With Plant Hosts - Santamaría, Laura; Reverón, Inés; Plaza-Vinuesa, Laura; Oliveros, Juan Carlos; de las Rivas, Blanca; Muñoz, Rosario; López de Felipe, Félix (Frontiers in Microbiology, 2019)
Oleuropein (OLE) is a secoiridoid unique to Oleaceae known to play a role in the plant-herbivore interaction. However, it is not clear how this molecule is induced to mediate plant responses to microbes and how microbes, in turn, withstand with OLE. To better understand how OLE affects the plant-microbe interaction, the contribution of differential gene expression in the adaptation to OLE was characterized by whole genome transcriptional profiling in Lactobacillus plantarum, a bacterium associated to the olive. OLE downregulated functions associated to rapid growth, remodeled membrane phospholipid biosynthesis pathways and markedly repressed the expression of several ABC transporters from L. plantarum. Genes encoding the plantaricin and lamABDCA quorum-sensing (QS) systems were down-regulated indicating the potential of OLE as a QS-antagonist. Notably, OLE diminished the expression of a set of genes encoding inmunomodulatory components and reoriented metabolic pathways to increase protein acetylation, probably to attenuate plant immunity. Responses were also triggered to repress the transport of acetoin and to buffer reactive oxygen species accumulation, two signals involved in plant development. The results suggest that OLE could act as a signaling molecule in the plant-microbe interaction and facilitate the accommodation of beneficial microbes such as L. plantarum by the plant host, via controlled expression of bacterial molecular players involved in this reciprocal interplay.